An analysis of employee welfare levels study at trimega bangun persada company - Prince Charles Heston Runtunuwu (Institute of Accounting Research and Novation (IARN), 2022)
The purpose of this study was to find out how the influence of education level on the welfare of employees at PT. Trimega Bangun Persada, and also to find out how long working hours affect the welfare of employees at PT. Trimega Bangun Persada analysis tool used is Multiple Linear Regression analysis tool, with a total sample of 50 (fifty) employees. The results of this study indicate that: The level of education has a significant positive effect on the dependent variable or welfare. Which means increasing the level of education will affect the level but welfare of employees. Significantly and positively too, the variable length of work has an effect on well-being. Which means that the length of time working can affect the level of employee welfare.